The Effect of Wayang Huruf Interactive Learning Media on Letter Recognition Skills in Children Aged 4–5 Years - Mutiara; Herman; Harlisa Harianti; Muharram; Yusnia (Jurnal CARE (Children Advisory Research and Education), 2026)
Early childhood literacy development is in its initial stages and remains heavily influenced by learning experiences that are concrete, repetitive, interactive, and aligned with children's developmental characteristics. This study aims to examine the impact of interactive learning media specifically "letter puppets" on the letter recognition skills of children aged 4–5 years. A quantitative approach was employed using a quasi-experimental design (specifically, a non-equivalent group design). The study involved 16 children, evenly divided into experimental and control groups. Data collection was conducted through observation, pre-test and post-test evaluations, and documentation. The experimental group received instruction using letter puppet media, while the control group used alphabet posters. The results indicate a significant improvement in letter recognition skills among children who learned using the letter puppet media. Improvements were observed in the ability to recognize letter sounds, identify letter shapes, and locate letters within words. Data analysis using the Wilcoxon Signed-Rank test revealed a difference in children's letter recognition abilities before and after the intervention with letter puppet media in the experimental group. The Wilcoxon test was used to compare pre-test and post-test scores for letter recognition within the experimental group. The test results showed a significance value (Sig. 2-tailed) of 0.012. Since the p-value (0.012) is less than 0.05, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. Thus, there is a significant difference in children's letter recognition abilities before and after the intervention using the interactive letter puppet learning media.